TGF-β1 expression and mesangial alterations in rat glomeruli of an experimental chronic nephrosis model - Uzunalan, Mümin; Seçkin, İsmail and Emincik, Aslı and Demirci Delipınar, Sibel and Ayaz Pekpak, Meltem and Köktürk, Sibel and Sönmez, Hüseyin Avni and Saraç, Elif Yaprak and Güngör, Zeynep Banu (Cerrahpaşa Medical Journal, 2019)
Objective: Puromycine aminonucleoside nephrosis (PAN) is extensively used as an experimental model of proteinuria following podocyte injury. In PAN animal models, nephrotic syndrome with minimal change disease and focal segmental sclerosis-like nephritis is demonstrated to be similar to that in human; however, the real mechanism of PAN is not yet elucidated. Evidence shows that transforming growth factor-β1 (TGF-β1) plays a key via stimulating matrix protein synthesis of both glomerular epithelial and mesangial cells. In this study, we aimed to examine the relationship between TGF-β expression and accumulation in mesangial matrix (MM) by the changes in renal function and ultrastructure alterations in renal glomeruli of the chronic PAN induced rats. Methods: Twelve male Wistar albino rats were divided into two groups: control group (n=6), chronic group (n=6). All data was statistically analyzed by One-way ANOVA Test. Results: Proteinuria levels in the chronic nephrosis groups were greater than the control (p<0.0025) whereas the levels of serum albumin and creatinine clearances were progressively decreased (p<0.05). TGF-β1 expression and MM were both significantly increased in PAN değerlegroup. Ultrastructural images of glomeruli of PAN showed apoptotic endothelium and mesangial cells, interstitial collagen and macrophages in increased MM. Conclusion: Our findings suggest that chronic PAN application induces a nephrotic syndrome, leading to renal impairment by TGF-β1 expression in glomeruli, increase in MM, formation of abundant interstitial collagen, and migration of macrophages. We suggest that chronic PAN progressively increases TGF-β1 expression and apoptosis following expansion of mesangial matrix in the affected glomeruli. This study needs further researches to determine the main source and signal pathway of TGF-β1 expression by double staining methods. Cite this article as: Seçkin İ, Uzunalan M, Ayaz Pekpak M, Köktürk S, Sönmez HA, Güngör ZB. TGF-β1 expression and mesangial alterations in rat glomeruli of an experimental chronic nephrosis model. Cerrahpasa Med J 2019; 43(1): 6-12.